Association between breast arterial calcifications found on mammography and coronary artery calcifications in asymptomatic Saudi women - Ahmed L. Fathala; Faisal Mohammed Alabdulkarim; Mohamed Shoukri; Muhannad Alanazi (Annals of Saudi Medicine, 2018)
BACKGROUND: Currently, there are no data on the prevalence of breast arterial calcification (BAC) in Saudi women. Furthermore, there are no data on the relationship between BAC and coronary artery calcium score (CACS) as a coronary artery disease (CAD) risk factor in Saudi women who undergo mammography. OBJECTIVE: Examine the role of BAC as a potential female-specific risk factor for CAD in Saudi women in order to investigate the relationship between BAC and CACS in women who undergo a screening mammography, and study the relationship between BAC and CAD risk factors, including age, diabetes mellitus, hypertension, chronic kidney disease (CKD), dyslipidemia, and family history of CAD. DESIGN: Retrospective, medical records review. SETTING: Single tertiary care center. PATIENTS AND METHODS: The study cohort included women who had mammograms and a CACS scan, and for whom data on CAD risk stratification and CAD risk factors had been collected within one year of each other from 2014 to 2017. Women with CAD were excluded from the study. MAIN OUTCOME MEASURES: Breast arterial calcification as a marker for coronary artery disease. SAMPLE SIZE: 307 Saudi women. RESULTS: BAC was found in 142 (46%) patients in the study population. BAC+ women were significantly older than the BAC– women (P=.001), and a strong association was found between BAC and CACS (P=.0001), diabetes (P=.0001), hypertension (P=.021), and CKD (P=.0031). However, no association was found between BAC and tobacco smoking, dyslipidemia, and family history of CAD. In addition, a strong correlation was found between CACS and the components of the BAC score (P<.001). Multivariate linear regression analysis revealed that age, CAC, and CKD are the only strong predictors of BAC. CONCLUSIONS: The proportion of BAC in Saudi women is 46%, and there may be a strong association between BAC and CAC, age, hypertension, and CKD. A large-scale prospective research study is necessary to validate the role of BAC on screening mammography as a CAD risk stratification tool and before routine reporting of BAC on a mammography report. LIMITATIONS: Because this was a retrospective study, patient selection bias cannot be excluded. CONFLICT OF INTEREST: None.